287 Acute and late echocardiographic and cardiac MRI findings in multisystem inflammatory syndrome in children. (8th December 2021) - Sirico, Domenico; Basso, Alessia; Reffo, Elena; Cavaliere, Annachiara; Castaldi, Biagio; Sabatino, Jolanda; Meneghel, Alessandra; Martini, Giorgia; Da Dalt, Liviana; Zulian, Francesco; Di Salvo, Giovanni
Abstract: Aims: Multisystem Inflammatory Syndrome in Children (MIS-C) is a severe condition affecting children previously exposed to SARS-CoV-2. The aim of our study was to describe the acute and late cardiac abnormalities in patients with MIS-C, evaluated by speckle-tracking echocardiography (STE) and cardiac MRI (CMR). Methods and results: Twenty-three (13 M, 10 F) patients with confirmed MIS-C diagnosis were recruited. All children underwent standard TTE, STE with analysis of LV global longitudinal strain (GLS). Seventeen (75%) were evaluated with CMR. All children received standard therapy. During follow-up echocardiography and CMR were repeated. Mean age was 8.1 ± 4 years. The majority (78.2%) was Caucasian. Cardiovascular symptoms were present in 10 (43.5%). Nine children (39.1%) shared Kawasaki Disease-like symptoms. Four patients (17.4%) needed ICU admission and three required inotropic support. Short-term survival was 100%. All patients showed a hyperinflammatory state. Tn-I was abnormal (>34 ng/l) in 15 patients (65.2%), BNP was elevated in 20 (86.9%). Median time to STE evaluation was 8 days and to CMR 18 days since fever onset. Mean LVEF and RVEF were, respectively, 59 ± 10% and 45 ± 7%. Coronary dilation was observed in six (26.1%) patients. STE showed reduced mean LVGLS (−17 ± 4.3%). LVEF on CMR was 60 ± 13%, LGE with non-ischaemic pattern was evident in 6/17 patients (35.2%). Median time to follow-up was 49 days for echocardiography and 200 days for CMR since disease onset. STE showed improvement of LVGLS (−18.8 ± 2.2%), while CMR displayed persistence of LGE in two patients and reduction or absence in two of the six patients previously diagnosed. Conclusions: The elevation of myocardial necrosis markers, the myocardial injury testified by reduced LVGLS and the presence of LGE on CMR in about a quarter of the patients support the hypothesis of a post-viral immune-mediated myocarditis-like pathogenesis of MIS-C. Early follow-up shows improvement of STE and CMR findings corroborating the evidence of excellent short-term survival.